A Comparative study to quantify the area of obturating material, sealer and voids in root canals obturated with Resilon/Epiphany and gutta-percha with different sealers - Vikram, M; Shetty, N; Singh, VP (Nepal Journal of Medical Sciences, 2014)
Background: Complete obturation of the root canal with an inert filling material and creation of a fluid-tight seal are among the major goals of successful endodontic treatment. Methods: Extracted mandibular premolar teeth were decoronated, prepared in a crown-down fashion and irrigated with 2.5% sodium hypochlorite and 17% EDTA. The specimens were randomly assigned into 4groups (n=10/each) and obturated with gutta-percha and Resilon/Epiphanywith different sealers. Horizontal sections were obtained of the coronal, middle and apical third at levels of 14-mm, 8-mm and 2-mm from the apex respectively and were viewed under magnification. The area of obturating material, sealer and voids were calculated using Image Jsoftware. Statistical comparisons between the Resilon and gutta-percha groups were made with Kruskal-Wallis Test and intergroup comparisions were made by Mann-Whitney U test with Bonferroni correction. Results: The results of this study showed that root canals obturated with gutta-percha or Resilon with Epiphany as sealer had significantly less area of sealer plus voids and voids alone as compared to root canals obturated with gutta-percha and AH Plus as sealer or gutta-percha and GuttaFlow. Conclusion: From the results of this study it can be concluded that methacrylate resin-based sealer Epiphany will lead to a better obturation of the root canals and adhesive sealers hold a better prospective. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 8-13 DOI: http://dx.doi.org/10.3126/njms.v3i1.10342